2019
DOI: 10.1111/anae.14837
|View full text |Cite
|
Sign up to set email alerts
|

Can high‐flow nasal oxygen redefine our end‐point for pre‐oxygenation?

Abstract: We read with interest the study by Shippam et al. [1] regarding high-flow humidified nasal oxygen (HFNO) for pre-oxygenation of pregnant women in preparation for general anaesthesia. The findings from this study do not support the use of HFNO to pre-oxygenate term pregnant women. The primary end-point used was an end-tidal oxygen fraction (F ET O 2 ) ≥ 0.9 which is a recommended target for pre-oxygenation by the Obstetric Anaesthetists' Association [2] and the Difficult Airway Society. However, with the advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Apnoeic oxygenation has shown promise in other patient populations , yet we did not investigate this in the current study due to obvious ethical implications in parturients. Some have suggested that if arterial desaturation could be slowed with high‐flow nasal oxygen following induction, it might not be a prerequisite to pre‐oxygenate to a value of ETO 2 ≥ 90% . Indeed, if a lower pre‐oxygenation endpoint was used (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apnoeic oxygenation has shown promise in other patient populations , yet we did not investigate this in the current study due to obvious ethical implications in parturients. Some have suggested that if arterial desaturation could be slowed with high‐flow nasal oxygen following induction, it might not be a prerequisite to pre‐oxygenate to a value of ETO 2 ≥ 90% . Indeed, if a lower pre‐oxygenation endpoint was used (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…oxygenate to a value of ETO 2 ≥ 90% [22]. Indeed, if a lower pre-oxygenation endpoint was used (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Tanna and Saha for their interest in our study and for raising a thought‐provoking discussion about the potential for lowering end‐tidal oxygen fraction endpoint in obstetric patients when using high‐flow nasal oxygenation.…”
Section: Theoretical Constructs For Time To Arterial Desaturation Commentioning
confidence: 99%